EFFECT OF HEPARIN, ESTROGEN ON EPIDIDYMAL SPERM CAPACITATION AND IN VITRO FERTILIZATION IN IRAQI SHEEP - & Saleh, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was designed to study the capacitation of caudal spermatozoa in vitro by different levels of heparin, estrogen for in vitro fertilization (IVF) in the Iraqi local sheep. Results of sperm capcitation (massive motility percentage) by applying three levels of heparin (50, 100, 150) IU in relation to breeding season showed no significant differences during breeding season with the three levels, which were (82.23 ± 0.58), While results by applying the higher level of heparin (150) IU out of breeding season showed significantly (P<0.05) more and active motility Which were (62.07 ± 0.62) than the other levels (56.85 ± 0.61). At the same time applications result of three estrogen levels (20, 40, 60) mg on sperm capcitation showed Positive relationship between concentrations and (massive motility percentage), which showed the highest concentration gave the best results during and out of breeding season (87.20 ± 0.60) and (65.86 ± 0.62) respectively. with significant differences (P<0.05) between the three levels. While the results of the in vitro fertilization (IVF) index which reflected the sperm capcitation were recorded with the highest estrogen concentration during breeding season (22.70 %) compared with the best heparin level (20 %) while she was (10.45 %), (8.70 %) out of breeding season Sequentially, in which the highest estrogen concentration gives a best capacitation and IVF index level compared with the high heparin level over the year.